The Effect of Container Type and Fermentation Period Towards Cocoa Beans Quality in Tidore Island - Mustamin Anwar Masuku; Syamsul Bahri; Nurjanna Albaar; Irwan Makarunggala (Universitas Khairun, 2022)
The purpose of this study was to determine the effect of wooden box containers on the quality of fermented cocoa beans. The experimental design used was Completely Randomized Design (CRD) with one factor, namely the length of fermentation consisting of each treatment repeated 3 times so that 9 experiments were obtained. The results obtained are analyzed for variance and if there is a significant difference between treatments, the Dancen test will be carried out. By the results of the treatment and discussion, it can be concluded that after fermenting cocoa beans using wooden boxes, the results obtained were an increase in the fermentation index of dry cocoa beans on the 3rd to 5th days (0.243, 1.147 and 2.027). This number indicates a change in color from purple to brown. Furthermore, the yield of dry cocoa beans, the content of moldy beans, and the skin content were at quality levels B and C and the water content and fat content still met the requirements of SNI-2323-2008. Polyphenols as antioxidants are in the range of 0.06 - 0.08.Â Based on this research it is also recommended that the fermentation process of beans use wooden boxes because it meets the requirements of the Indonesian National Standard for Cocoa Quality Number 2323-2008.